Determination of Nutritional Status of Some Vegetables Grown with Different Water Resource Applications in Sargodha, Pakistan: Different Nutritional Values of Some Vegetables (Biological Sciences - PJSIR, 2021)
Proximate and nutritional concentrations of some vegetables irrigated with different types of water were determined in present study. Allium fistulosum showed highest concentrations of N and P at site3 and site1, respectively. Highest ash concentration in Trigonella foenum-graecum demonstrated high mineral concentration of this vegetable. The crude protein contents ranged from 15.38% to 26.19% and crude fiber contents ranged from 12.81% to 16.73% in all vegetables. The tannins and saponins contents showed significant (P